Interleukin 6 reduces vascular smooth muscle cell apoptosis via Prep1 and is associated with aging. Issue 11 (22nd October 2021) - Cimmino, Ilaria; Prisco, Francesco; Orso, Sonia; Agognon, Ayewa L.; Liguoro, Pasquale; De Biase, Davide; Doti, Nunzianna; Ruvo, Menotti; Paciello, Orlando; Beguinot, Francesco; Formisano, Pietro; Oriente, Francesco
Abstract: Aging exacerbates neointimal formation by reducing apoptosis of vascular smooth muscle cells (VSMCs) and induces inflammation within vascular wall. Prep1 is a homeodomain transcription factor which stimulates the expression of proinflammatory cytokines in aortic endothelial cell models and plays a primary role in the regulation of apoptosis. In this study, we have investigated the role of Prep1 in aorta of Prep1 hypomorphic heterozygous mice ( Prep1 i/+ ) and in VSMCs, and its correlation with aging. Histological analysis from Prep1 i/+ aortas revealed a 25% reduction in medial smooth muscle cell density compared to WT animals. This result paralleled higher apoptosis, caspase 3, caspase 9 and p53 levels in Prep1 i/+ mice and lower Bcl‐xL. Prep1 overexpression in VSMCs decreased apoptosis by 25% and caspase 3 and caspase 9 expression by 40% and 37%. In parallel, Bcl‐xL inhibition by BH3I‐1 and p53 induction by etoposide reverted the antiapoptotic effect of Prep1. Experiments performed in aorta from 18 months old WT mice showed a significant increase in Prep1, p16 INK4, p21 Waf1 and interleukin 6 (IL‐6) compared to youngest animals. Similar results have been observed in H2 O2 ‐induced senescent VSMCs. Interestingly, the synthetic Prep1 inhibitory peptide Prep1 (54–72) reduced the antiapoptotic effects mediated by IL‐6, particularly in senescent VSMCs. These results indicate that IL‐6‐Prep1 signaling reduces apoptosis, by modulating Bcl‐xL and p53 both in murine aorta and in VSMCs. In addition, age‐dependent increase in IL‐6 and Prep1 in senescent VSMCs and in old mice may be involved in the aging‐related vascular dysfunction.